Boy proof - Castellucci, Cecil, 1969- (Cambridge, Mass. : Candlewick Press, 2005)
Feeling alienated from everyone around her, Los Angeles high school senior and cinephile Victoria Denton hides behind the identity of a favorite movie character until an interesting new boy arrives at school and helps her realize that there is more to life than just the movies.
600
Accelerated Reader AR
Keywords: Identity -- Fiction; Motion picture industry -- Fiction; Motion pictures -- Fiction; High schools -- Fiction; Schools -- Fiction; Interpersonal relations -- Fiction; Los Angeles (Calif.) -- Fiction